Study of the effects of Limnocharis Flava (yellow velvetleaf) on wastewater quality from oil palm production - Fitri Yanti, Sukirman (2010)

(untitled)
Malaysia is world biggest exporter of quality palm oil. Oil palm in Malaysia was contributing 50% of world production. From palm oil processing, a large amount of solid wastes such as palm trunks, palm fronds, empty bunches and palm shell are generated. These wastes offer problems to environment if not treated and properly dealt with. There are many ways to treat the POME. One of the alternative treatment methods was biological treatment, by using of emergent aquatic plants which was Limnocharis Flava. The research had two objectives: 1) to investigate an optimal design condition whereby emphasis was placed on waste water circulation and 2) to study the feasibility of Limnocharis Flava in Palm Oil Mill Effluents (POME)treatment system. The aquatic plant treatment method consisted of 4 plastic containers which 7 gal of each capacity and aquarium pump. This experiment consisted of three condition in which: the wastewater only (control 1), POME and aquatic plants without circulation (control 2), and the last one is POME, aquatic plant and the existence of circulation (sample) from a container to another one. The experiments were conducted in 9days to reduce the contaminants such as TSS, COD, BOD and Oil and Grease. The effectiveness of treatment using aquatic plants only were the second highest, while wastewater treatment plants without the plants and circulation give the most lowest percentage during the process of removal of organic material. The greatest percentage removal of contaminated materials when the existence of aquatic plants and circulation where 97.48% of Oil and grease was removed followed by the percent removal of BOD, TSS and COD were 86.6%, 82.65% and 76% respectively.